Parenchymal-sparing hepatectomies (PSH) for bilobar colorectal liver metastases are associated with a lower morbidity and similar oncological results: a propensity score matching analysis. Issue 9 (September 2016) - Memeo, Riccardo; de Blasi, Vito; Adam, René; Goéré, Diane; Azoulay, Daniel; Ayav, Ahmet; Gregoire, Emilie; Kianmanesh, Reza; Navarro, Francis; Sa Cunha, Antonio; Pessaux, Patrick; ,
Abstract: Objective: The aim of this study is to evaluate whether a parenchymal-sparing strategy provides similar results in terms of morbidity, mortality, and oncological outcome of non-PSH hepatectomies in a propensity score matched population (PSMP) in case of multiple (>3) bilobar colorectal liver metastases (CLM). Background: The surgical treatment of bilobar liver metastasis is challenging due to the necessity to achieve complete resection margins and a sufficient future remnant liver. Two approaches are adaptable as follows: parenchymal-sparing hepatectomies (PSH) and extended hepatectomies (NON-PSH). Methods: A total of 3036 hepatectomies were analyzed from a multicentric retrospective cohort of hepatectomies. Patients were matched in a 1:1 propensity score analysis in order to compare PSH versus NON-PSH resections. Results: PSH was associated with a lower number of complications (≥1) (25% vs. 34%, p = 0.04) and a lower grade of Dindo-Clavien III and IV (10 vs. 16%, p = 0.03). Liver failure was less present in PSH (2 vs. 7%, p = 0.006), with a shorter ICU stay (0 day vs. 1 day, p = 0.004). No differences were demonstrated in overall and disease-free survival. Conclusion: In conclusion, PSH resection for bilobar multiple CLMs represents a valid alternative to NON-PSH resection in selected patients with a reduced morbidity and comparable oncological results.